Public Motivation for Hiking Activities in Kota Kinabalu, Sabah - Jesleen Linus Dani; Andy Russel Mojiol (e-VIBS, Faculty of Science and Natural Resources, 2022)
It is undeniable that the popularity of hiking activities has gradually increased over the years, particularly in Sabah. Therefore, people are looking for activities that will help them both physically and socially. Henceforth, this study aims to investigate the public’s motivation for participating in hiking activities in Kota Kinabalu, Sabah. The instrument's reliability was confirmed by Cronbach's alpha test, which generated a result of 0.947. A total of 109 respondents took part in this study, via social media platforms such as WhatsApp. The Chi-square test was used to explain the relationship between the recreation motivation and demographic variables (age, gender, education level). However, the result showed that there was no significant relationship between the public’s motivation to participate in hiking activities and demographic variables.